ARTIFICIAL INTELLIGENCE DALAM DUNIA PENDIDIKAN: SEBUAH PENDEKATAN HOLISTIK - Kholis (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
Artificial Intelligence (AI) is playing an increasingly important role in education, providing innovative solutions for adaptive learning, academic data analysis, and administrative automation. However, AI implementation in education faces challenges, particularly in ethics, technological accessibility, and educator readiness. This study explores the benefits, challenges, and optimal strategies for AI adoption in education using a qualitative approach. Systematic literature review and in-depth interviews with 10 education and technology experts were conducted. Thematic analysis revealed that AI enhances learning experiences through personalized content and real-time feedback. However, challenges such as infrastructure limitations and low digital literacy among educators persist. Additionally, parental involvement and AI integration into curricula are key factors in successful implementation. The findings offer insights into how AI can be optimally utilized in education and provide recommendations to enhance institutional readiness for AI adoption.